ANALISIS STRATEGI KOMUNIKASI PEMASARAN MEDIA DIGITAL DALAM MEMBANGUN LOYALITAS KONSUMEN PT. ERAJAYA SWASEMBADA TBK. - Muhamad Rezaldiansyah; Emilianshah Banowo (Program Studi Ilmu Komunikasi, Universitas Muhammadiyah Bengkulu, 2026)
This study analyzes PT. Erajaya Swasembada Tbk.’s digital marketing communication strategies in fostering customer loyalty. Motivated by Indonesia’s growing e-commerce sector and internal analytics showing rising traffic but fluctuating channel effectiveness, the research uses a qualitative descriptive approach within a constructivist paradigm, focusing on the Eraspace platform. Data were collected via in-depth interviews, social media observation, and campaign documentation, analyzed using Miles & Huberman’s interactive model, and validated through triangulation. Findings indicate that integrated marketing communication, personalization, storytelling, loyalty programs, and after-sales service enhance engagement and repeat purchases, though challenges remain in channel consistency, deeper personalization, and conversion optimization. Keywords : integrated marketing communication; digital marketing communication; customer loyalty; relationship marketing; qualitative case study